2019
DOI: 10.1177/0033354919874088
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A and Hepatitis B Vaccination Coverage Among Persons Who Inject Drugs and Have Evidence of Hepatitis C Infection

Abstract: Objectives: Despite recommendations for vaccination against hepatitis A virus (HAV) and hepatitis B virus (HBV) for all adults at increased risk of infection, several US states have reported increases in HAV and HBV infections among persons who inject drugs. We investigated hepatitis A and hepatitis B vaccination coverage among a sample of persons who reported injecting drugs and had evidence of hepatitis C virus (HCV) infection. Methods: We searched the Wisconsin Immunization Registry for the vaccination reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
17
2
Order By: Relevance
“…25 Another study among PWID with evidence of HCV infection found higher proportions of HAV and HBV susceptibility; however, these findings were based on records of vaccination history, not serological measures. 26 Although we found that age was inversely related to HBV susceptibility, significant proportions of all age groups in our study did not have HBV immunity. The proportion of HBV susceptibility was higher among participants born during 1990-1999 than among participants born before 1990, suggesting that HBV vaccination may not be resulting in comprehensive coverage.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…25 Another study among PWID with evidence of HCV infection found higher proportions of HAV and HBV susceptibility; however, these findings were based on records of vaccination history, not serological measures. 26 Although we found that age was inversely related to HBV susceptibility, significant proportions of all age groups in our study did not have HBV immunity. The proportion of HBV susceptibility was higher among participants born during 1990-1999 than among participants born before 1990, suggesting that HBV vaccination may not be resulting in comprehensive coverage.…”
Section: Discussioncontrasting
confidence: 65%
“…1,24 Although studies on the seroprevalence of HAV and HBV susceptibility among SSP participants are limited, some studies were conducted among similar populations. 23,25,26 One study conducted among PWID found higher proportions of HAV and HBV susceptibility than our study did. 23 A study using a nationally representative sample also found higher proportions of HAV and HBV susceptibility than our study did.…”
Section: Discussioncontrasting
confidence: 62%
“…Since 1996, ACIP has recommended HepA vaccination for persons who use injection or noninjection drugs ( 6 ). Despite this longstanding recommendation, HAV seropositivity remains low (20%–40%) in this population ( 13 , 99 , 100 ).…”
Section: Hav Backgroundmentioning
confidence: 95%
“…We use the term "PWUD" referring to those who use illicit substances including opioids. While a few prior studies have examined Hepatitis A virus (HAV) and Hepatitis B virus (HBV) vaccination among PWUD in the US, these studies are often limited in geographic coverage and sample size [28][29][30]. Information on receipt of other recommended vaccinations among PWUD is limited [31].…”
Section: Introductionmentioning
confidence: 99%